Biodiversity, Roles, and Potency of Bacteria in Agricultural Land - Wahyu Purbalisa; Dian Hendrayanti; Wahida Annisa Yusuf (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Biotic and abiotic factors influence biodiversity. Environment and human activities change biodiversity. Human activities to get their food through agricultural activities affect the diversity of bacteria in agricultural lands. Cultivation techniques, plant species, plant growth stadia, and soil influence the diversities of bacteria in agricultural land. The dominant bacteria on agricultural land are from the phyla Proteobacteria, Actinobacteria, Acidobacteria, Bacteroidetes, and Firmicutes. Proteobacteria play a role in the nitrogen, carbon, and sulphur cycles, Actinobacteria in the carbon cycle, and Acidobacteria in the nitrogen cycle. Bacteroidetes work as decomposers of organic matter. Firmicutes are required for biocontrol and plant growth. The high use of pesticides in agricultural land has decreased the diversity of bacteria. Indigenous bacteria that survive in the condition of high pesticide residue contamination have the potential as remediation agents for pesticide residues. Indigenous bacteria can degrade pesticide residues through oxidation-reduction and complexation reactions, thereby reducing the level of pesticide contamination.